The Application of Hadith on Morality among Hadith Studies Students at UIN Sumatera Utara Medan - Nabila Yunita; Dahlia Lubis (al-Afkar, Journal For Islamic Studies, 2026)
The rapid development of technology today is accompanied by various moral problems in society, such as the rise of online gambling, drug abuse, promiscuity, and the decline of respect toward parents and teachers. This phenomenon indicates a moral crisis that has also affected higher education. This study aims to analyze the application of hadiths on morality in the daily lives of Hadith Studies students at UIN Sumatera Utara Medan and to identify the factors influencing it. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using a descriptive-analytical technique. The results show that the application of moral hadiths among students is still partial and inconsistent, influenced by factors such as the campus environment, family, and social interactions. Nevertheless, there are efforts to internalize moral values through both academic and non-academic activities. This study concludes that strengthening the implementation of moral hadiths requires an integrative approach involving curriculum development, lecturers’ role modeling, and a supportive social environment. Therefore, it is recommended to enhance systematic and sustainable moral development programs within the university environment.